THE FIRST RECORD OF THE GENUS $ARGIOPE$ OF THE FAMILY ARANEIDAE: $ARGIOPE$ $BRUENNICHI$ (SCOPOLI, 1772) AND $ARGIOPE$ $LOBATA$ (PALLAS, 1772) IN ARMENIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
The article presents the first record of the genus Argiope, orb-weaver spiders from the Araneidae family in Armenia. The two female specimens of Argiope bruennichi (Scopoli, 1772) were found in the Lori Region (northern part), and two specimens of the female spider of Argiope lobata (Pallas, 1772) were recorded in the Tavush Region (north-eastern part) and Armavir Region (south-western part) of Armenia in 2020–2022.
Keywords: new records; spider; distribution; $Argiope~bruennichi$; $Argiope~lobata$; spider of Caucasus